2017
DOI: 10.1111/1758-2229.12554
|View full text |Cite
|
Sign up to set email alerts
|

Thermal sensitivity of bacteriocytes constrains the persistence of intracellular bacteria in whitefly symbiosis under heat stress

Abstract: Temperature affects the persistence of diverse symbionts of insects. Our previous study indicates that the whitefly symbionts confined within bacteriocytes or scattered throughout the body cavity outside bacteriocytes may have differential thermal sensitivity. However, the underlying mechanisms remain largely unknown. Here, we report that following continuous heat stress, Portiera and Hamiltonella were almost completely depleted in two species of Middle East-Asia Minor 1 (MEAM1) and Mediterranean (MED) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…The results of our study showed a significant dissimilarity in the midgut composition across temperature regimen. Our results are in contrast to several studies that have demonstrated a reduction in the richness of endosymbionts or complete eradication of midgut microbes in insects as a result of temperature increases [17][18][19][20] . Our studies and those studies demonstrate that temperature has an effect on gut microbes but our results may not translate to other insects sampled in other laboratories or other mosquitoes sampled in this laboratory at a different time.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of our study showed a significant dissimilarity in the midgut composition across temperature regimen. Our results are in contrast to several studies that have demonstrated a reduction in the richness of endosymbionts or complete eradication of midgut microbes in insects as a result of temperature increases [17][18][19][20] . Our studies and those studies demonstrate that temperature has an effect on gut microbes but our results may not translate to other insects sampled in other laboratories or other mosquitoes sampled in this laboratory at a different time.…”
Section: Discussioncontrasting
confidence: 99%
“…The impact of temperature change on the midgut microbiome diversity of insects has mainly been studied with constant temperature. The results of such studies show a significant reduction in the richness of the midgut microbiome to complete loss of midgut microbiome as well as reduction in the vertical transmission to the next generation [17][18][19][20] . Given that temperatures fluctuate in nature; using constant temperature to study the impact of temperature on the midgut microbiome may not provide an accurate depiction.…”
mentioning
confidence: 99%
“…A new infection of S-symbionts is through occasional events of horizontal transmissions among different insect species or different individuals mediated by plant, parasitoids, or copulation [ 44 , 45 , 46 , 47 , 48 ]. High temperatures can eliminate the mutualistic partners from insect hosts; many bacteriocyte-associated symbionts have reduced densities or are lost entirely when the insect host is exposed to high temperatures [ 49 , 50 , 51 ]. Our experimental populations did not contact other infectious populations, species, or host plants fed by other infectious populations and were kept in controlled conditions in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of indirectly affecting the host's stress or immune responses, symbionts may themselves produce and release heat shock proteins or metabolites that directly protect the host or other microbes that the host depends on (i.e., obligate symbionts) . Obligate symbionts are often a thermal "weak link" and more susceptible to temperature extremes than their hosts (Corbin et al, 2017;Shan et al, 2017;Zhang et al, 2019). Shielding an obligate symbiont from thermal damage would therefore benefit both the host and all of its symbionts.…”
Section: Introductionmentioning
confidence: 99%